Study of Anaemia and Its Associated Risk Factors among Pregnant Women in a Rural Field Practice Area of a Medical College - Khan, Nazia Aram M; Sonkar, Venkat Ramana K; Domple, Vijay K; Inamdar, Ismail A (National Journal of Community Medicine, 2017)
Background: Anaemia in pregnancy accounts for one fifth of maternal death worldwide. The association between anaemia and adverse pregnancy outcome, higher incidence of preterm & low birth weight deliveries has been demonstrated. Objective: This research was conducted to study the prevalence of anaemia among pregnant women in the rural field practice area of a medical college and also to study some risk factors associated with anaemia among pregnant women. Materials and Method: A community-based cross-sectional study was carried out among 350 pregnant women from August 2015 to December 2015 in the rural population of Mudkhed , Maharashtra. The study participants were selected by using simple random sampling method. The hemoglobin estimation was done. Data were collected and analyzed with SPSS version 16. Results: Overall prevalence of the anaemia among pregnant women was found to be 84.85%. Various socio-demographic factors like Age, Education of women, Socioeconomic class, Gravid status, Gestational age, were found to be significantly associated with anaemia in pregnancy. Conclusion: High prevalence of anemia among pregnant women indicates anaemia to be a major public health problem in the rural community. Factors such as socioeconomic status, and educational status contribute to this high prevalence.